Non-aqueous electrolyte for lithium battery and lithium battery containing non-aqueous electrolyte
By using a non-aqueous electrolyte of a specific chemical formula, including 1,1,1-trifluoro-2,3-dimethoxypropyl (TFDMP) and lithium difluorosulfonimide (LiFSI), in lithium metal batteries, the solution is The problems of electrolyte decomposition and battery life in lithium metal batteries have been achieved, and higher stability and high rate performance have been achieved.
Patent Information
- Application Number
- CN202380050689.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-28
- Filing Date
- 2023-06-28
- Publication Date
- 2025-02-14
AI Technical Summary
Due to the high reactivity and uneven surface of lithium metal in lithium metal batteries, a stable interface cannot be formed between the electrolyte and the lithium metal electrode, and an electrolyte decomposition reaction occurs, increasing the battery resistance and shortening the battery life.
A nonaqueous electrolyte represented by the specific chemical formula 1 is used, which contains 1,1,1-trifluoro-2,3-dimethoxypropyl (TFDMP) as a solvent and lithium difluorosulfonimide ( LiFSI) is a lithium salt with a concentration of between 0.5M and 4.0M.
This non-aqueous electrolyte significantly improves the stability of lithium metal batteries, inhibits the decomposition reaction of the electrolyte, extends the battery life, and improves the high-rate charging performance.
Smart Images

Figure CN119452497A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a non-aqueous electrolyte for lithium metal batteries which is suitable for lithium metal batteries containing lithium metal as negative electrode active material to improve the overall performance of the battery and a lithium metal battery containing the non-aqueous electrolyte. Background Art
[0002] With the rapid development of the electronics, communications, and computer industries, the application scope of energy storage technology has gradually expanded to cameras, mobile phones, laptops, desktop computers, and even electric vehicles. Therefore, high-performance secondary batteries that are lightweight, long-lasting, and highly reliable are also being developed.
[0003] Among the secondary batteries currently in use, lithium secondary batteries developed in the early 1990s have been selected as the power source for many portable devices due to their high operating voltage and ultra-high energy density compared to traditional batteries such as Ni-MH, Ni-Cd, and sulfuric acid-lead batteries using aqueous electrolytes.
[0004] Lithium metal, carbon-based materials, silicon, etc. are used as negative electrode active materials for these lithium secondary batteries. Among them, lithium metal has the advantage of obtaining the highest energy density, and therefore research is continuously being conducted.
[0005] Lithium electrodes using lithium metal as an active material are usually made by attaching lithium foil to a flat copper or nickel foil as a current collector. Alternatively, lithium foil itself is used as a lithium electrode without a separate current collector, or a battery is assembled using only a current collector without lithium foil, and then a lithium metal layer is formed by charging and discharging the battery to be used as a negative electrode (anodeless method).
[0006] However, the problem with lithium secondary batteries containing lithium metal electrodes is that due to the high reactivity of lithium metal and the surface unevenness that occurs during the electrodeposition and stripping of lithium metal on the electrode when the battery is charged and discharged, a stable interface cannot be formed between the electrolyte and the lithium metal electrode, and electrolyte decomposition reactions continue to occur.
[0007] The products of the electrolyte decomposition reaction act as a resistance layer that hinders the stripping and deposition of lithium, which not only increases the battery resistance sharply, but also causes the electrolyte and available lithium in the battery to be depleted, thus causing the problem of battery life degradation. Summary of the invention
[0008] An object of the present invention is to provide a non-aqueous electrolyte having excellent stability against lithium metal, so as to solve the above-mentioned problems.
[0009] Another object of the present invention is to provide a non-aqueous electrolyte solution that is excellent in battery stability and contains a negative electrode active material in addition to lithium metal.
[0010] The object of the present invention is to provide a lithium battery comprising the non-aqueous electrolyte. The object of the present invention is not limited to the above-mentioned object. Other objects and advantages of the present invention that are not mentioned can be understood through the following description and can be further understood more clearly through the embodiments of the present invention. In addition, it is obvious that the objects and advantages of the present invention can be achieved by the means in the claims and their combinations.
[0011] In order to solve the technical problem, the present invention provides a compound represented by the following Chemical Formula 1. [Chemical Formula 1]
[0012]
[0013] In chemical formula 1,
[0014] R 1 , R 2 and R 3 are independently hydrogen and an alkyl group having 1 to 5 carbon atoms;
[0015] R 1 , R 2 and R 3 When it is an alkyl group having 1 to 5 carbon atoms, X is F, Cl, Br or I;
[0016] n is an integer from 1 to 5;
[0017] m, o, and p are integers from 0 to 3.
[0018] In order to solve the above technical problems, the present invention provides a non-aqueous electrolyte for a lithium battery comprising a solvent represented by the following Chemical Formula 1 and a lithium salt.
[0019] [Chemical formula 1]
[0020]
[0021] In chemical formula 1,
[0022] R 1 , R 2 and R 3 are independently hydrogen and an alkyl group having 1 to 5 carbon atoms;
[0023] R 1 , R 2 and R 3 When it is an alkyl group having 1 to 5 carbon atoms, X is F, Cl, Br or I;
[0024] n is an integer from 1 to 5;
[0025] m, o, and p are integers from 0 to 3.
[0026] According to an embodiment of the present invention, the solvent represented by Chemical Formula 1 is 1,1,1-trifluoro-2,3-dimethoxypropan (TFDMP) represented by the following Chemical Formula 1a.
[0027] [Chemical formula 1a]
[0028]
[0029] According to an embodiment of the present invention, the lithium salt contained in the non-aqueous electrolyte may be lithium bis(fluorosulfonyl)imide (LiFSI).
[0030] According to an embodiment of the present invention, the concentration of the lithium salt contained in the non-aqueous electrolyte is 0.5M to 4.0M (mol / L).
[0031] According to an embodiment of the present invention, the solvent of Chemical Formula 1 may include 50 volume percent to 100 volume percent relative to 100 volume percent of the non-aqueous solvent.
[0032] To solve the technical problem, the present invention can provide a lithium secondary battery, preferably comprising: a positive electrode containing a positive electrode active material; a negative electrode containing a negative electrode active material; a separator sandwiched between the negative electrode and the positive electrode; and a non-aqueous electrolyte for a lithium battery.
[0033] According to an embodiment of the present invention, the negative electrode active material may be lithium metal.
[0034] According to an embodiment of the present invention, the negative electrode active material may be a silicon-based negative electrode active material.
[0035] According to an embodiment of the present invention, the positive electrode active material may be one or more selected from the group consisting of composite oxides of cobalt, manganese, nickel, aluminum, iron or a combination of these metals and lithium.
[0036] The technical solutions described above do not list all the features of the present invention. The various features of the present invention and its advantages and effects can be further understood in detail in conjunction with the following specific embodiments.
[0037] The non-aqueous electrolyte of the present invention has the following beneficial effects.
[0038] The non-aqueous electrolyte of the present invention has excellent stability to lithium metal, and thus can suppress the decomposition reaction of the electrolyte. When used in a lithium metal battery, the battery life performance and high-rate charging performance can be improved.
[0039] The non-aqueous electrolyte of the present invention has excellent stability not only for lithium metal but also for batteries containing other negative electrode active materials, thereby improving the life characteristics and high rate performance of the battery.
[0040] In addition to the above-mentioned beneficial effects, the specific effects of the present invention will be described together with the specific contents required to implement the present invention below. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It shows the chemical structural formula and characteristics of the solvents contained in Example 1 and Comparative Examples 1 and 2;
[0042] Figure 2 It shows the LSV evaluation results of the electrolytes of Example 1 and Comparative Examples 1 and 2;
[0043] Figure 3 The figure shows the Coulomb efficiency evaluation results of lithium metal batteries containing the electrolytes of Example 1 and Comparative Examples 1 and 2;
[0044] Figure 4 The FE-SEM images of the aluminum surface confirmed after the aluminum corrosion (Al corrosion) evaluation was performed using the electrolytes of Example 1 and Comparative Examples 1 and 2;
[0045] Figure 5 It shows the full battery performance comparison results of lithium metal batteries containing the electrolytes of Example 1 and Comparative Examples 1 and 2;
[0046] Figure 6 The high rate life evaluation results of the lithium metal battery (NP ratio = 2.5) containing the electrolyte of Example 1 are shown;
[0047] Figure 7 The high rate life evaluation results of the lithium metal battery (NP ratio = 1) containing the electrolyte of Example 1 are shown;
[0048] Figure 8 The figure shows the initial coulombic efficiency evaluation results of the lithium battery (containing silicon as the negative electrode active material) containing the electrolyte of Example 2 and Comparative Example 3;
[0049] Fig. 9 The graph shows the high rate life evaluation results of lithium batteries (containing silicon as the negative electrode active material) containing the electrolyte solutions of Example 2 and Comparative Example 3. DETAILED DESCRIPTION
[0050] The principle of the preferred embodiment of the present invention is described in detail below in conjunction with the drawings and descriptions. However, the following drawings and the descriptions described below are preferred implementation methods among the many methods required to effectively describe the features of the present invention, so the present invention is not limited to the following drawings and descriptions.
[0051] The terms "first", "second" and the like may be used to describe various components, but the terms are only used to distinguish one component from other components. For example, the first component may be named after the second component, and similarly, the second component may be named after the first component.
[0052] The singular form also includes the plural form unless otherwise indicated in the text. The terms "including" or "having" used in this specification are used to specify the features, numbers, steps, actions, components, accessories or combinations thereof described in the specification, and do not preclude the existence or additional possibility of one or more other features or numbers, steps, actions, components, accessories or combinations thereof.
[0053] Unless otherwise specified, all terms used herein, including technical or scientific terms, have the same meaning as those generally understood by those skilled in the art. Terms defined in commonly used dictionaries have the same meaning as those in technical texts and should not be interpreted in an abnormal or excessive manner unless otherwise clearly defined in this specification.
[0054] The present invention is described in further detail below.
[0055] First, according to the present invention, the so-called "lithium metal battery" refers to a battery using lithium metal (Lithium metal) as a negative electrode.
[0056] The present invention relates to an electrolyte for a lithium metal battery including a solvent represented by the following Chemical Formula 1.
[0057] [Chemical formula 1]
[0058]
[0059] In chemical formula 1,
[0060] R 1 , R 2 and R 3 are independently hydrogen and an alkyl group having 1 to 5 carbon atoms;
[0061] If R 1 , R 2 and R 3 is an alkyl group having 1 to 5 carbon atoms, then X is F, Cl, Br or I;
[0062] n is an integer from 1 to 5;
[0063] m, o, and p are integers from 0 to 3.
[0064] The inventors of the present invention have repeatedly studied the solvents of non-aqueous electrolytes suitable for lithium metal batteries containing lithium metal as negative electrode active materials. As a result, it was found that when the solvent of Chemical Formula 1, which changes the main chain structure of the conventionally commonly used DME (1,2-dimethoxyethane: 1,2-dimethoxyethane) solvent, is applied to lithium metal batteries, the stability exhibited is significantly improved compared with the existing electrolytes, and as a result, the characteristics of various electrochemical properties including the life of lithium metal batteries are greatly improved, thereby completing the present invention (see Figure 1 ).
[0065] According to an embodiment of the present invention, the solvent represented by the above-mentioned [Chemical Formula 1] may be 1,1,1-trifluoro-2,3-dimethoxypropan (TFDMP) represented by the following Chemical Formula 1a.
[0066] [Chemical formula 1a]
[0067]
[0068] Lithium metal electrodes used in lithium metal batteries are due to their low dropout voltage (-3.04V vs. SHE), high theoretical capacity (3860mAhg -1 ), low density (0.544gcm -3 ) is a very effective negative electrode material for improving the energy density of lithium-based batteries. Furthermore, when lithium metal electrodes are used together with high-voltage positive electrode materials, they have the advantage of significantly improving the energy density of batteries.
[0069] However, lithium metal batteries have a problem of shortening the life of the battery due to the formation of lithium dendrites during charging and the consumption of the electrolyte by side reactions between the electrolyte and lithium metal.
[0070] Therefore, in order to solve the above problems and achieve high energy density, an excellent electrolyte is needed that can suppress side reactions with lithium metal through stable electrochemical performance and further, can be used together with high voltage positive electrode materials with outstanding oxidation stability.
[0071] The compound of the chemical formula 1 for the solvent of the non-aqueous electrolyte of the present invention contains a halogen-containing group (-CX 3According to a specific embodiment, the compound represented by the chemical formula 1a contains a fluorine-containing group (-CF 3 ) and containing ether groups.
[0072] Generally speaking,
[0073] When a fluorine-containing group is contained in a molecule, the HOMO (highest occupied molecular orbital) energy level of the molecule decreases due to the high electronegativity of fluorine. The decreased HOMO energy level can improve the oxidation stability of the molecule.
[0074] Furthermore, the compound represented by Chemical Formula 1a according to one embodiment of the present invention has only one-group fluorine-containing group, thereby reducing side effects (reduced solvation degree, reduced salt solubility, etc.) when having multiple fluorine-containing groups.
[0075] In summary, due to the presence of fluorinated groups (-CF 3 ), so when used as a solvent for a non-aqueous electrolyte, it is believed that the oxidation stability of the electrolyte can be improved, and this was verified in the LSV evaluation experiment described later.
[0076] Under the condition that the oxidation stability of the electrolyte used in lithium metal batteries is guaranteed, the energy density can be greatly improved when the lithium metal electrode is used with a high-voltage positive electrode material such as a high-nickel (High-Nickel) positive electrode material or a high-manganese (High-manganese or Over-lithiated Oxide).
[0077] The solvent for the electrolyte of the present invention is designed from the viewpoint of molecular design so as not to cause the carbon (-CX 3 ) directly binds to oxygen atoms, thus providing a binding site for lithium ions, which has the beneficial effect of increasing the solvation power of lithium ions. The solvents containing fluorine-containing groups used in previous lithium metal batteries have the phenomenon of reducing the solvation power while causing the carbon where the fluorine-containing groups are located to directly bind to oxygen atoms. However, the solvent used in the electrolyte of the present invention is believed to increase the solvation power of lithium ions due to the above-mentioned molecular structure, thereby obtaining excellent electrochemical performance.
[0078] According to an embodiment of the present invention, an electrolyte for a lithium metal battery includes lithium bis(fluorosulfonyl)imide (LiFSI) as a lithium salt.
[0079] In addition to LiFSI, lithium salts that can be included include LiCl, LiBr, LiI, LiClO, which are commonly used in electrolytes. 4 , LiBF 4 , LiB 10 Cl 10 、LiPF 6 、LiAsF 6 、LiSbF 6 、LiAlCl 4 、LiSCN、LiC 4 BO 8 、LiCF 3 CO 2 、LiCH 3 SO 3 、LiCF 3 SO 3 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 ,LiC 4 F 9 SO 3 、LiC(CF 3 SO 2 ) 3 ,(CF 3 SO 2 ) 2 NLi, lithium chloroborate, lower aliphatic carbonate Lihium, lithium tetraphenylborate, lithium imide, etc.
[0080] Here, the total concentration of LiFSI and other lithium salts in the electrolyte is 0.5M (mol / L) to 4.0M, preferably 1.0M to 3.0M. At such a salt concentration, the side reaction between lithium metal and the electrolyte can be suppressed, and the corrosion of the positive electrode collector and the prevention of the dissolution of the transition metal of the positive electrode active material can be ensured. When the concentration of the lithium salt is too high, there may be problems such as performance degradation due to low ion conductivity and decreased electrolyte impregnation due to high viscosity, so it can be appropriately adjusted within the range.
[0081] In addition, the solvent of the chemical formula 1 may include 50 volume percent to 100 volume percent of the non-aqueous solvent, and the remaining volume may include carbonate solvents, ester solvents, etc. described later.
[0082] The electrolyte of the present invention may include a cyclic fluorinated carbonate solvent together with the solvent of Chemical Formula 1. The cyclic fluorinated carbonate solvent is generally used as a cyclic fluorinated carbonate solvent for the electrolyte solvent, and is not particularly limited if it is a compound in which at least 2 or more hydrogens are replaced by fluorine. Specifically, the cyclic fluorinated carbonate solvent may be one or more selected from the group consisting of fluoroethylene carbonate, difluoroethylene carbonate, and trifluoromethyl ethylene carbonate, preferably fluoroethylene carbonate.
[0083] In addition to the cyclic fluorinated carbonate solvent, the electrolyte solution of the present invention may include one or more solvents selected from the group consisting of chain carbonate, chain ester and chain ether solvents (hereinafter referred to as chain solvents) as the non-aqueous solvent.
[0084] The chain solvent may be used without limitation as long as it is a chain solvent generally used in an electrolyte solution of a lithium secondary battery.
[0085] Specifically, the chain carbonate may be one or more selected from the group consisting of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethylmethyl carbonate, methyl propyl carbonate, and ethylpropyl carbonate.
[0086] The chain ester may be one or more selected from the group consisting of methylacetate, ethylacetate, propylacetate, methylpropionate, ethylpropionate and propylpropionate. The chain ether may be one or more selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether and ethyl propyl ether.
[0087] Preferably, the one or more solvents selected from the group consisting of the linear carbonates, linear esters and linear ethers may be one or more solvents selected from the group consisting of dimethyl carbonate, diethyl carbonate, methyl propionate, ethyl propionate, dimethyl ethyl ether and diethyl ether.
[0088] In addition, the electrolyte of the present invention can also be supplemented with additives for forming SEI films according to needs to improve the overall performance of the battery. The additives for forming SEI films that can be used in the present invention are vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (Fluoroethylene carbonate; FEC), lithium difluorophospate (LiPO2F2), lithium bis(oxalato)borate (LiBOB), lithium difluoro(oxalato)borate (LiFOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorobisoxalato phosphate (WCA), lithium bis(fluoroethylsulfonyl)borate (LiFOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorobisoxalato phosphate (WCA), lithium bis(fluoroethylsulfonyl)borate (LiFOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorobisoxalato phosphate (WCA), lithium bis(fluoroethylsulfonyl)borate (LiFOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis( ... bis(pentafluoroethylsulfonyl)amide, LiBETI), lithium(malonato oxalato)borate, LiMOB, LiPF 2 C 4 O 8 、LiSO 3 CF 3 、LiPF 4 (C 2 O 4 )、LiP(C 2 O 4 ) 3 、LiC(SO 2 CF 3 ) 3 , LiBF 3 (CF 3 CF 2 )、LiPF 3 (CF 3 CF 2 ) 3 , Li 2 B 12 F 12, 1,3-propanesultone, 1,3-propanesultone, biphenayl, cyclohexyl benzene, 4-fluorotoluene, succinic anhydride, ethylene sulfate anhydride, tris(methylsilyl)borate, cyclic sulfite, saturated sultone, unsaturated sultone, non-cyclic sulfone, etc. are used alone or in combination of two or more, and are not limited thereto. The additive for forming the SEI film can contain 0.5 weight percent to 10 weight percent relative to the total weight of the electrolyte to form an excellent film.
[0089] Lithium Metal Batteries
[0090] According to one embodiment of the present invention, a lithium metal battery comprising the above-mentioned non-aqueous electrolyte is provided. Specifically, the lithium metal battery comprises a positive electrode, a negative electrode containing lithium metal as an active material, and a separator, and the electrolyte comprises the electrolyte of the present invention.
[0091] (1) Positive electrode
[0092] The positive electrode includes a positive electrode active material layer coated on a positive electrode current collector. The positive electrode active material layer may include a positive electrode active material, a binder, and may selectively contain a conductive material.
[0093] The positive electrode current collector is not particularly limited as long as it does not cause chemical changes in the battery and has high conductivity. For example, stainless steel, aluminum, nickel, titanium, carbon electrodes can be used, or the surface of aluminum or stainless steel can be surface treated with carbon, nickel, titanium, silver, etc. Here, the positive electrode current collector can be in various forms such as a film, sheet, foil, net, porous body, foam, non-woven fabric, etc., with fine concavoconvexity formed on the surface to increase the adhesion with the positive electrode active material.
[0094] The positive electrode active material is a compound that can implement reversible lithiation and delithiation of lithium, and specifically, can include one or more metals such as cobalt, manganese, nickel or aluminum and a lithium composite metal oxide containing lithium. More specifically, the lithium composite metal oxide can be exemplified by a lithium-manganese oxide (e.g., LiMnO 2 、LiMn 2 O 4 etc.), lithium-
[0095] Cobalt-based oxides (such as LiCoO 2 etc.), lithium-nickel-based oxides (such as LiNiO 2 etc.), lithium-nickel-manganese-based oxides (such as LiNi 1-Y Mn Y O 2 (where 0 < Y < 1), LiMn 2-z Ni z O 4 (where 0 < Z < 2) etc.), lithium-nickel-cobalt-based oxides (such as, LiNi 1-Y1 Co Y1 O 2 (where 0 < Y1 < 1) etc.), lithium-manganese-cobalt-based oxides (such as, LiCo 1-Y2 Mn Y2 O 2 (where 0 < Y2 < 1), LiMn 2-z1 Co z1 O 4 (where 0 < Z1 < 2) etc.), lithium-nickel-manganese-cobalt-based oxides (such as, Li(Ni p Co q Mn r1 )O 2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1, p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O 4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2) etc.), or lithium-nickel-cobalt-transition metal (M) oxides (such as, Li(Ni p2 Co q2 Mn r3 M S2 )O 2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg and Mo, p2, q2, r3 and s2 are the atomic separations of the respective independent elements, 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < s2 < 1, p2 + q2 + r3 + s2 = 1)) etc., and may include one or more of these compounds.
[0096] Among them, from the perspective of improving the capacity performance and stability of the battery, the lithium composite metal oxide can be LiCoO 2 , LiMnO 2 , LiNiO 2 , lithium nickel manganese cobalt oxide (such as, Li(Ni 1 / 3 Mn1 / 3 Co 1 / 3 ) 2 、Li(Ni 0.6 Mn 0.2 Co 0.2 ) 2 、Li(Ni 0.5 Mn 0.3 Co 0.2 ) 2 、Li(Ni 0.7 Mn 0.15 Co 0.15 ) 2 and Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 etc.) or lithium nickel cobalt aluminum oxide (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 ) 2 etc.
[0097] As another example, the positive electrode active material can be composed of elemental sulfur (S8); Li2Sn ( n≥ 1 ), 2,5-dimercapto-1,3,4-thiadiazole, 1,3,5-trithiocyanuric acid, etc. disulfides, organic sulfides or carbon-sulfur polymers ((C2Sx)n: x = 2.5 to 50, n≥2 ) and the like.
[0098] The positive electrode active material may contain 80 weight percent to 99 weight percent based on the total weight of the solid content in the positive electrode slurry. Here, when the content of the positive electrode active material is less than 80%, the energy density will decrease, and thus the capacity will decrease.
[0099] Binders are used to bind the electrode active material and the conductive material and to bind the current collector. Non-limiting examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polymethacrylic acid (PMA), polymethyl methacrylate (PMMA), polyacrylamide (PAM), polymethacrylamide, polyacrylonitrile (PAN), polymethacrylonitrile, polyimide (PI), alginic acid, alginate, chitosan, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof.
[0100] Conductive materials are used to further improve the conductivity of the electrode active material. There are no particular restrictions on such conductive materials as long as they do not cause chemical changes in the battery and have conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as Super-P, carbon black, acetylene black, Ketjen black, channel black, furnace black, lampblack, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; polyphenylene derivatives, etc.
[0101] (2) Negative electrode
[0102] The negative electrode of the present invention is a lithium metal negative electrode using lithium metal as a negative electrode active material. The lithium metal negative electrode used when assembling a lithium metal battery can be formed only by a current collector, or can be formed in the form of coating lithium metal on the current collector, or can be formed only by lithium metal.
[0103] The negative electrode current collector is not particularly limited as long as it does not cause chemical changes in the battery and has conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, carbon electrode, copper, or a surface treatment of stainless steel with carbon, nickel, titanium, silver, etc., aluminum alloy-cadmium alloy, etc. can be used. And its form can be a film, sheet, foil, net, porous body, foam, non-woven fabric, etc. with fine concavoconvex or not formed on the surface. For example, copper foil can be used as the negative electrode current collector, but it is not limited to this.
[0104] The thickness of the current collector is not particularly limited, but preferably 5 to 100 μm, more preferably 5 to 50 μm. If the thickness of the current collector is less than 5 μm, the difficulty of processing may increase, and if it exceeds 100 μm, the battery thickness and weight may increase unnecessarily, which may affect the battery performance, such as reduced energy density, etc., so the above range is preferred.
[0105] When a negative electrode consisting only of a current collector is used when assembling a battery, lithium ions moved from the positive electrode by initial charge and discharge are irreversibly plated on the negative electrode current collector to form a lithium metal layer after the battery is assembled, and then the lithium metal layer can function as a negative electrode active material layer. Here, when an electrode made only of a current collector is used as a negative electrode, the current collector may include metal and metal oxide particles to uniformly induce plating.
[0106] Alternatively, starting from the battery assembly, a negative electrode containing an active material, namely lithium metal, may also be used, and there is no particular restriction on the method of coating the negative electrode current collector with lithium metal. As an example, a method of rolling after laminating a lithium metal film on the current collector, and a method of electrolytically or electrolessly plating lithium metal on the current collector may be used. Here, the thickness of the lithium metal layer of the negative electrode is not particularly limited, but may be 10 μm or more or 20 μm or more and 50 μm or less or 40 μm or less.
[0107] For a lithium metal negative electrode made of lithium metal alone, the thickness thereof is not particularly limited but may be 10 μm or more or 20 μm or more and 50 μm or less or 40 μm or less.
[0108] According to another embodiment of the present invention, the non-aqueous electrolyte can be applied to other negative electrodes besides lithium metal.
[0109] Specifically, the negative electrode of the present invention and the solvent of the present invention as the negative electrode active material can also be applied to an electrode using a silicon-based active material such as Si or SiOx. In this case, the negative electrode is prepared by coating a mixture of a negative electrode active material, a conductive agent and a binder on a negative electrode collector, and then drying and pressing.
[0110] (3) Diaphragm
[0111] The separator is used to separate the negative electrode from the positive electrode and to provide a passage for the movement of lithium ions. Any separator that can be conventionally used in lithium batteries can be used. Furthermore, a separator that has low resistance to the movement of electrolyte ions and excellent electrolyte impregnation ability can be used. For example, a separator selected from glass fiber, polyester, polytetrafluoroethylene, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or a combination thereof, can also be in the form of a non-woven fabric or a woven fabric.
[0112] For example, a polyolefin polymer separator such as polyethylene, polypropylene, or a separator containing a coating of a ceramic component or a polymer substance may be used to ensure heat resistance or mechanical strength, and these separators may have a single-layer or multi-layer structure. In one embodiment, as the separator, a separator made of a ceramic coating material containing ceramic particles and an ion binder polymer coated on both sides of a polyolefin polymer substrate may be used.
[0113] According to one embodiment of the present invention, a lithium metal battery comprising the positive electrode, the negative electrode, the separator and the electrolyte of the present invention is provided. Here, the shape of the lithium metal battery is not particularly limited, and various shapes such as cylindrical, soft-pack, button, etc. can be adopted.
[0114] The above preferred embodiments are only used to illustrate the technical solutions of the present invention and help to understand, but not to limit them; although the present invention is described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify and change the technical solutions described in the above embodiments, and these modifications and changes do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions described in the embodiments of the present invention. The following embodiments are only one embodiment of the present invention, and the present invention is not limited to the following embodiments.
[0115] [Example]
[0116] Production Example 1 (Production of TFDMP)
[0117] 600 milliliters (mL) of dry THF and 1 mol (24 g) of NaH were added to a 1 liter (L) round-bottom flask and stirred for 20 minutes at 0°C under an argon atmosphere. Then, 0.4 mol (54 g) of 1,1,1-trifluoro-2,3-propanediol was slowly added using a syringe pump. After adding 1,1,1-trifluoro-2,3-propanediol, the mixture was further stirred at 0°C for 1 hour to prepare the mixture. And at 0°C, 1 mol (62.4 mL) of iodomethane was added dropwise to the mixture. The mixture was stirred at room temperature for 2 hours and refluxed overnight while slowly heating. Then, the liquid portion of the mixture was fractionally distilled using a 60 cm fractionating column, and the distillation process was performed three times to obtain the final product (TFDMP).
[0118] (1) Production of non-aqueous electrolyte
[0119] The electrolytes of the embodiments and comparative examples were prepared by the combination of Table 1. In the following table, DME represents 1,2-dimethoxyethane, DMP represents 1,2-dimethoxypropane, EC represents ethylene carbonate, DEC represents diethyl carbonate, and FEC represents fluoroethylene carbonate. The concentration (M) of the lithium salt is the number of moles (mol) of the lithium salt per 1 liter (L) of solvent contained in the electrolyte. All electrolytes were prepared in a glove box filled with an inert gas.
[0120]
Table 1
[0121]
[0122] (2) Manufacturing of positive electrode
[0123] Using NCM 811(LiNi 0.8 Co 0.1 Mn 0.1 O 2 ) as the positive electrode active material, Super-P as the conductive material, polyvinylidene fluoride (PVdF) as the binder, and N-methylpyrrolidone as the solvent to prepare a positive electrode active material slurry with a weight ratio of active material: conductive material: binder of 8:1:1. Then, the positive electrode active material slurry was coated on one side of an aluminum foil, and then rolled and dried to produce a positive electrode with a loading of 5.0 mg / cm 2 The positive electrode.
[0124] (3) Manufacturing of negative electrode
[0125] Lithium metal electrode
[0126] As the negative electrode, a lithium metal foil having a thickness of 20 μm (manufactured by China Energy Lithium Corporation) was used.
[0127] Silicon electrode
[0128] The negative electrode was manufactured using micro silicon (Micro Si) as the negative electrode active material. Specifically, micro silicon (Micro Si) was used as the negative electrode active material, carboxymethyl cellulose (CMC) was used as the binder, Super-P was used as the conductive material, and distilled water was used to prepare a negative electrode active material slurry with a weight ratio of active material: conductive material: binder of 92:4:4. Then, the negative electrode active material slurry was coated on one side of the copper foil and then rolled and dried to produce a negative electrode with a loading of 5.0 mg / cm 2 of the negative electrode.
[0129] (4) Full-cell production
[0130] The separator and the lithium metal foil of (3) were stacked on the positive electrode of (2), and then a Swagelok type cell or a 2032-type button cell stacked in the order of negative electrode / separator / positive electrode was manufactured in a glove box. Celgard 2400 product (manufactured by Celgard) formed of polyethylene was used as a separator, the N / P ratio was set to 2.5, and 40 μl of the electrolyte of Example 1, Comparative Examples 1 and 2 was injected to produce a full battery.
[0131] The separator and the micron silicon of (3) were stacked on the positive electrode of (2), and then a Swagelok type cell or a 2032-type button cell stacked in the order of negative electrode / separator / positive electrode was manufactured in a glove box. Celgard 2400 product (manufactured by Celgard) formed of polyethylene was used as the separator, the N / P ratio was set to 2.5, and 40 μl of the electrolyte of Example 2 and Comparative Example 3 was injected to produce a full battery.
[0132] Evaluation Example 1: Oxidation stability evaluation
[0133] The oxidation stability of the electrolytes of Example 1 and Comparative Examples 1 and 2 was evaluated by linear sweep voltammetry (LSV) analysis. Specifically, a Li / Al half cell was prepared, and after injecting the electrolytes of Example 1 and Comparative Examples 1 and 2, the voltage was increased from the open circuit voltage (OCV) to 5.0V (vs. Li / Li + ) until 0.5mVs -1 The LSV analysis method was implemented at a scan rate of . The evaluation results are as follows Figure 2 shown.
[0134] according to Figure 2It can be confirmed that the electrolyte of Example 1 (TFDMP) reaches about 4.8V (vs. Li / Li + ) does not start a large oxidation current. On the contrary, the electrolyte of Comparative Example 1 (DME) is at 4.0V (vs. Li / Li + ), the electrolyte of Comparative Example 2 (DMP) is at 4.4V (vs.Li / Li + ) and the oxidation current is rapidly started near the surface of the electrolyte. This result shows that the oxidation stability of the electrolyte containing the solvent of the present invention is very outstanding.
[0135] Evaluation Example 2: Coulombic Efficiency
[0136] In order to confirm the reversibility of the electrolytes of Example 1 and Comparative Examples 1 and 2 when used in lithium metal batteries, coulombic efficiency evaluation was performed.
[0137] Specifically, a Li / Cu half-cell was prepared, and the electrolytes of Example 1 and Comparative Examples 1 and 2 were added and 1 mA cm -2 The Coulombic efficiency was evaluated while the current was applied. In the Li / Cu half-cell, lithium ions can be deposited (plating) and re-stripped (stripping) on Cu with the applied current. The ratio of the amount of lithium ion deposited and the amount of re-stripping is used as the Coulombic efficiency. The results are shown in Figure 3 shown.
[0138] according to Figure 3 It can be confirmed that the coulombic efficiency of the half-cell including the electrolytes of Comparative Examples 1 and 2 varies greatly in the entire cycle region, which is judged to be caused by the generation of unstable SEI and irreversible lithium ion deposition. On the contrary, it can be confirmed that the half-cell including the electrolyte of Example 1 exhibits a relatively stable coulombic efficiency in the entire cycle region.
[0139] Evaluation Example 3: Aluminum corrosion evaluation
[0140] Aluminum corrosion evaluation was performed to evaluate the oxidation stability of the electrolytes of Example 1 and Comparative Examples 1 and 2. Aluminum foil is used as the current collector of the positive electrode. If corrosion occurs on the aluminum surface due to the reaction between aluminum and the electrolyte under oxidizing conditions, the performance of the positive electrode may be adversely affected due to increased surface resistance, etc.
[0141] Specifically, a Li / Al half-cell was prepared, and after adding the electrolytes of Example 1 and Comparative Examples 1 and 2, 5.0 V (vs. Li / Li+) was applied (Constant voltage experiment) for 24 hours. After the half-cell was decomposed, the surface of aluminum was observed using FE-SEM (Field emission scanning electron microscopy; Tescan Mira3 LMFE) to confirm the corrosion of aluminum ( Figure 4 ).
[0142] Figure 4 The figure shows the aluminum surface of the half-cell using the electrolytes of Example 1 and Comparative Examples 1 and 2. The half-cell using the electrolytes of Comparative Examples 1 and 2 shows very serious aluminum surface corrosion (such as cracks and flakes), whereas the aluminum surface of the half-cell using the electrolyte of Example 1 shows no cracks and is very smooth.
[0143] Evaluation Example 4: Full Cell Performance Evaluation
[0144] Full cells containing the electrolytes of Example 1 and Comparative Examples 1 and 2 were prepared and subjected to 1.0 C-ratio (1.6 MA cm -2 ) current to charge / discharge, the life performance of the full battery is evaluated, and the results are as follows Figure 5 It can be confirmed that the battery containing the electrolyte of Example 1 showed 100% retention until 450 cycles and showed excellent stability, whereas the battery containing the electrolyte of Comparative Example 1 experienced life performance degradation within 60 cycles, and the battery containing the electrolyte of Comparative Example 2 experienced life performance degradation within 175 cycles.
[0145] In addition, in order to observe the high rate life performance of the battery containing the electrolyte of the present invention, a 3.0 C-ratio (4.8 MA cm -2 ) current, the life performance of the full battery was evaluated, and the results are as follows Figure 6 It can be confirmed that the battery containing the electrolyte of the present invention has good performance even at a 3.0C-rate (4.8MA cm -2 ) under high current charge / discharge conditions, it also showed a retention rate of 93% over 550 cycles, demonstrating excellent performance.
[0146] A 0.5 C-rate (2 MA cm -2 ) and 1.0C-ratio (4.0MA cm-2 ) current, the battery life performance was evaluated, and the results are as follows Figure 7 The results show that the battery containing the electrolyte of the present invention has a 0.5C-rate (2MA cm -2 ) current applied, showed a retention of 81% after 200 cycles, and at 1.0 C-rate (4.0 MA cm -2 ) also showed a retention rate of 88% for 145 cycles under the condition of current application.
[0147] A full cell containing the electrolytes of Example 2 and Comparative Example 3 was prepared, and the initial coulombic efficiency and high rate life performance were observed. The results are as follows: Figure 8 , Fig. 9 shown.
[0148] It can be confirmed that the battery containing the electrolyte of Example 2 shows an initial Coulomb efficiency of about 85.2%, and the battery containing the common electrolyte combination, that is, Comparative Example 3, shows an initial Coulomb efficiency of about 83.5% ( Figure 8 ).
[0149] In addition, the battery containing the electrolyte of Example 2 shows a retention rate of about 75% even at a high rate of 5.0C, and exhibits a stable coulombic efficiency throughout the cycle. On the contrary, the battery containing the electrolyte of the ordinary electrolyte combination, i.e., the electrolyte of Comparative Example 3, shows a retention rate of about 67%, and low coulombic efficiency at high rates can be observed ( Fig. 9 ).
[0150] From these results, it was confirmed that the electrolyte solution containing the solvent of the present invention can improve the electrochemical performance of lithium metal batteries or batteries containing silicon as a negative electrode active material.
[0151] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person skilled in the art can still modify or make equivalent substitutions for the technical solutions described in the aforementioned embodiments, and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions described in the embodiments of the present invention.
Claims
1. A compound, characterized in that It is represented by the following chemical formula 1; [Chemical formula 1] In chemical formula 1, R 1 , R 2 and R 3 are independently hydrogen and an alkyl group with a carbon number of 1 to 5; R 1 , R 2 and R 3 When it is an alkyl group having 1 to 5 carbon atoms, X is F, Cl, Br or I; n is an integer from 1 to 5; and m, o and p are integers from 0 to 3.
2. A non-aqueous electrolyte for a lithium battery, characterized in that: Containing a solvent represented by the following chemical formula 1 and a lithium salt; [Chemical formula 1] In chemical formula 1, R 1 , R 2 and R 3 are independently hydrogen and an alkyl group with a carbon number of 1 to 5; R 1 , R 2 and R 3 When it is an alkyl group having 1 to 5 carbon atoms, X is F, Cl, Br or I; n is an integer from 1 to 5; and m, o and p are integers from 0 to 3.
3. The non-aqueous electrolyte for lithium batteries according to claim 2, characterized in that: The chemical formula 1 is a compound represented by the following chemical formula 1a; [Chemical formula 1a] 4. The non-aqueous electrolyte for lithium batteries according to claim 2, characterized in that: The lithium salt is lithium bis(fluorosulfonyl)imide.
5. The non-aqueous electrolyte for lithium batteries according to claim 4, characterized in that: The concentration of the lithium salt is 0.5M to 4.0M (mol / L).
6. The non-aqueous electrolyte for lithium batteries according to claim 2, characterized in that: The solvent of the chemical formula 1 comprises 50 volume percent to 100 volume percent relative to 100 volume percent of the non-aqueous solvent.
7. A lithium battery, characterized in that: include: A positive electrode containing a positive electrode active material; a negative electrode containing a negative electrode active material; a separator sandwiched between the negative electrode and the positive electrode; and a non-aqueous electrolyte for a lithium metal battery according to claim 2.
8. The lithium battery according to claim 7, characterized in that: The negative electrode active material is lithium metal.
9. The lithium battery according to claim 7, characterized in that: The negative electrode active material is a silicon-based active material.
10. The lithium battery according to claim 7, characterized in that: The positive electrode active material is one or more selected from the group consisting of composite oxides of cobalt, manganese, nickel, aluminum, iron, or a combination of these metals and lithium.